2011
DOI: 10.2147/ndt.s10389
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for the treatment of post-traumatic stress disorder: a review

Abstract: Background:Post-traumatic stress disorder (PTSD) is a psychiatric sequel to a stressful event or situation of an exceptionally threatening or catastrophic nature. Cognitive behavioral therapy (CBT) has been used in the management of PTSD for many years. This paper reviews the effectiveness of CBT for the treatment of PTSD following various types of trauma, its potential to prevent PTSD, methods used in CBT, and reflects on the mechanisms of action of CBT in PTSD.Methods:Electronic databases, including PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(124 citation statements)
references
References 124 publications
(130 reference statements)
4
116
1
3
Order By: Relevance
“…Today, a variety of nonpharmacological interventions are available to the public for the control of stress and anxiety, with the most common being counseling and training by nurses and midwives as healthcare providers with a significant role in preventing pregnancy and postpartum stress and anxiety (22). Counseling or therapy is a stress management strategy that can be offered with a variety of different approaches, including the cognitive-behavioral approach (23).…”
Section: Introductionmentioning
confidence: 99%
“…Today, a variety of nonpharmacological interventions are available to the public for the control of stress and anxiety, with the most common being counseling and training by nurses and midwives as healthcare providers with a significant role in preventing pregnancy and postpartum stress and anxiety (22). Counseling or therapy is a stress management strategy that can be offered with a variety of different approaches, including the cognitive-behavioral approach (23).…”
Section: Introductionmentioning
confidence: 99%
“…74 In adults, the treatment literature indicates that effective PTSD interventions involve short-term and cognitive behavioral models. 75,76 Despite a growing literature base supporting the efficacy of these treatments for PTSD in noncancer populations, a limited number of studies have investigated treatment of PTSS in adolescent survivors of childhood cancer. Stemming from a model that conceptualizes the diagnosis of childhood cancer as a potentially traumatic event, Kazak et al 77 developed the Surviving Cancer Competently Intervention Program (SCCIP) for adolescent survivors of childhood cancer and their families.…”
Section: Treatment Of Ptss/ptsdmentioning
confidence: 99%
“…More specific and comprehensive reviews about the following topics can be found in the literature: prevalence, 15,[18][19][20] behavioral inhibition, [190][191][192] behavioral genetics, 48,52 genetics, 55,56,193,194 gene vs. environment interplay, 52,70 pathophysiology, 31,71 neural substrates, 71 normal development of fears, 195 psychopharmacological treatment, [196][197][198] and CBT. 164,[199][200][201] Conclusions Anxiety disorders are prevalent, associated with a number of negative life outcomes, and currently underrecognized and under-treated. The etiology involves both genes and environmental factors in a complex interplay.…”
Section: Preschool Children Treatment and Preventionmentioning
confidence: 99%